PENERAPAN MODEL PEMBELAJARAN CONNECTED MATHEMATICS PROJECT (CMP) DENGAN PENDEKATAN KONTEKSTUAL TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA SMP - Febriati Lydia Lidwina; Melyani; Rosmaiyadi; Nindy Citroresmi (De Fermat : Jurnal Pendidikan Matematika, 2021)
This study aims to determine whether the mathematical reasoning ability taught by the Connected Mathematics Project (CMP) model with a contextual approach is better than the direct learning model, to determine the students' KKM achievement in mathematical reasoning abilities taught using the Connected Mathematics Project (CMP) model with a contextual approach. , and to find out students' interest in learning when the Connected Mathematics Project (CMP) learning model with a contextual approach was applied to social arithmetic material for class VII. The population in this study were seventh grade students of SMPN 10 Singkawang and the samples in this study were Grade VII A and VII B students. The analysis technique was in the form of two sample t-test, right-hand t-test, right-hand z-test one sample, and the percentage of interest in learning. The results of the research are that the mathematical reasoning ability using the Connected Mathematics Project (CMP) model with a contextual approach is better than the direct learning model, students' mathematical reasoning abilities have reached the KKM and students' interest in learning is high.